Analisis Efektivitas E-Health Menggunakan Metode E-Govqual dan IPA Di Puskesmas Gading Kota Surabaya - Gissela Legong; Andriyan Rizki Jatmiko (FKOM UNIKU, 2024)
E-Health, a public service that leverages Information Technology to enhance the health sector's knowledge base, faces developmental challenges. At Gading Health Center in Surabaya City, dissatisfied assessments of the health center's rating stem from discontent with both services and the e-Health system. Issues include disparities in service time compared to the targeted e-Health Service System queue, as well as variations between online registration times and the actual services provided at the health center. Moreover, human resource factors such as knowledge, experience, and technological skills among Gading Community Health Center staff significantly influence the successful implementation of the e-Health system. This study employs e-GovQual and IPA methods to evaluate the effectiveness of e-Government Implementation, focusing on dimensions like efficiency, trust, reliability, and citizen support. The research findings, analyzing the effectiveness of e-Health at Puskesmas Gading using e-GovQual and IPA methods, lead to the conclusion that the implementation of e-Health at Puskesmas Gading in Surabaya City positively impacts the quality of health services